Meta‐analysis: efficacy of exclusive enteral nutrition as induction therapy on disease activity index, inflammation and growth factors in paediatric Crohn's disease. Issue 3 (24th June 2022) - Sohouli, Mohammad Hassan; Fatahi, Somaye; Farahmand, Fatemeh; Alimadadi, Hosein; Seraj, Shaikh Sanjid; Rohani, Pejman
Summary: Background: There is evidence of inconsistency in sequelae of exclusive enteral nutrition (EEN) as induction therapy in paediatric patients with Crohn's disease (CD). Aim: To investigate the potential effects of EEN on paediatric Crohn's disease activity index (PCDAI), inflammation and biochemical parameters in paediatric patients with CD. Methods: We performed a comprehensive systematic search of PubMed/MEDLINE, Web of Science, SCOPUS and Embase until 8 January 2022 regardless of the time of publication or language. Random‐effects model was applied to combine the datasets. The main outcomes were analysed through mean difference (MD) and its 95% confidence interval (CI). Results: Forty six studies met eligibility criteria and were included in the meta‐analysis. Pooled findings indicated that PCDAI score (MD of −27.24; 95% CI −31.84 to −22.64), calprotectin (MD of −842.83 mg/kg; CI −1018.24 to −667.42), CRP (pooled MD of −2.36 mg/dl; CI −2.68 to −2.03), and ESR (MD of −21.09 mm/h; CI −23.79 to −18.38), albumin (MD of 0.65 g/dl; CI 0.58 to 0.72), haemoglobin (MD of 1.12 g/dl; CI 0.87 to 1.37), weight (MD of 4.30 kg; CI 3.39 to 5.22), and height (MD of 0.98 cm; CI 0.35 to 1.62) improved significantly with EEN. Conclusions: Adherence to EEN can have significant, beneficial effects as induction therapy in paediatric patients with CD. Abstract : Beneficial effects of exclusive interal nutrition in children with Crohn's disease.